2020
DOI: 10.1590/0037-8682-0546-2019
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis vasculitis manifesting as ischemic stroke

Abstract: FIGURE 1: Axial DWI and T2-weighted MRI showing left hemipons infarction (arrows, A and B). Three-dimensional timeof-flight magnetic resonance angiography showing significant stenosis of the basilar artery (arrow, C). 2/2 Feitoza LM et al. -Neurosyphilis vasculitis OPEN ACCESS https://creativecommons.org/licenses/by/4.0/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…The entire M1 segment of the left MCA and the A1 segment of the left ACA were involved, suggesting a high possibility of arteritis. Previous studies have reported similar concentric enhancement in the BA due to syphilitic arteritis (3,4). Concentric enhancement on HR-MRI may help identify syphilitic arteritis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The entire M1 segment of the left MCA and the A1 segment of the left ACA were involved, suggesting a high possibility of arteritis. Previous studies have reported similar concentric enhancement in the BA due to syphilitic arteritis (3,4). Concentric enhancement on HR-MRI may help identify syphilitic arteritis.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the identification of neurosyphilis during the early stages of the disease is essential. Apart from serum or cerebrospinal fluid (CSF) findings of T. pallidum, high-resolution magnetic resonance imaging (HR-MRI) indicating arteritis can help differentiate neurosyphilis from strokes caused by other factors (3,4). Here, we present a unique case of progressive stroke caused by neurosyphilis and radiological characteristics of the intracranial vessel wall imaging.…”
Section: Introductionmentioning
confidence: 97%
“…Other recent case reports of strokes secondary to neurosyphilis reported these patients were HIV-infected. [13][14][15][16] This case report demonstrated the clinical heterogeneity of neurosyphilis and the importance of extending stroke workup in patients with ischemic stroke who lack common stroke risk factors, especially in HIV-infected patients. Clinicians should be familiar with the clinical presentation of posterior circulation strokes.…”
Section: Discussionmentioning
confidence: 73%
“…1 HR-VWI complements luminal imaging and can differentiate many potential causes of luminal narrowing. [2][3][4] Vessel wall enhancement usually corresponds to expected patterns of vessel wall inflammation and/or increased vasa vasorum density in distinct vascular pathologies 2 and can also detect cranial nerve enhancement, 4 as illustrated in this report. MRI with HR-VWI is a relevant tool to demonstrate TBM arteritis and can identify vessel wall enhancement without changes in the vessel caliber.…”
mentioning
confidence: 87%
“…1 Autoimmune mechanisms have also been suspected in these cases since they can appear even during effective treatment. The recent development of a new magnetic resonance imaging (MRI) sequencethe high-resolution vessel wall imaging (HR-VWI)has allowed submillimeter MRI evaluation of arterial walls [2][3][4] and can contribute to the diagnosis of this disease.…”
mentioning
confidence: 99%